FLUID INCLUSION STUDY OF THE WUNUGETUSHAN PORPHYRY CU-MO DEPOSIT, INNER MONGOLIA - Li N.; Lai Y.; Li W.B.; Chen Y.J. (My University, 2007)
The Wunugetushan porphyry Cu-Mo deposit, Inner Mongolia, occurs in the Erguna terrane which is bounded by the NE-trending Derbugan fault to the southeast. Within the Mongolia-Hinggan Orogen, the Erguna terrane evolved in the Paleozoic subduction related accretion and Early Mesozoic collision and Late Mesozoic-Cenozoic post-collision tectonics related to Pacific plate subduction. The Wunugetushan deposit, formed in Jurassic, is a typical example of porphyry ore systems developed in continental collision regime. Its geological and geochemical characteristics may be an ideal reference to understand the origin of porphyry ore-systems formed in collisional settings. This paper reports the research results on fluid inclusions obtained by microthermometric study and compositional identification using Laser Raman Spectroscope and Scanning Electron Microscope combined with Energy Spectrum. The hydrothermal ore-forming process of the Wunugetushan deposit includes three stages, i. e. the early, middle and late stages, characterized by mineral assemblages of quartz-potassic feldspar, quartz-sericite-polymetallic sulfides and illite-carbonate-quartz, respectively. In hydrothermal quartz three types of fluid inclusions can be observed. They are NaCl-H(2)O solution, daughter mineral-bearing, and CO(2)-rich. However, the latter two types cannot be observed in the late-stage quartz. Homogenization temperatures of fluid inclusions in early stage are above 510 degrees C, with the highest salinities up to 75. 8 wt% NaCl eqv. Fluid inclusions contain daughter minerals including halite, chalcopyrite and hematite which possibly represent an oxidizing environment. Vapor bubbles are mainly composed of CO(2), and the liquids are dominated by H(2)O and generally contain CO(3)(2-). Mo and Cu are mainly mineralized in the middle stage, and in the temperature spans of 510 degrees C similar to 340 degrees C and 340 degrees C similar to 240 degrees C, respectively, with fluid salinities ranging from 6.3 to 52.0 wt% NaCl eqv. In middle stage, daughter minerals in fluid inclusions, such as halite and chalcopyrite, except of hematite, can be recognized. The daughter mineral-bearng inclusions coexist with the vapor- and liquid-rich fluid inclusions. Fluid inclusions with contrasting salinities are homogenized to divergent phases at similar temperatures. These phenomena strongly suggest that fluid-boiling occurred in the middle stage. The homogenization temperatures of late stage fluid inclusions cluster into 240 degrees C similar to 100 degrees C, with corresponding salinities no more than 12. 4 wt% NaCl eqv. In a word, the early stage fluids are magmatic in origin and characterized by high temperature, high salinity, high oxygen-fugacity and CO(2)-rich. In middle stage, the fluids boiled and resulted in CO(2)-release, oxygen-fugacity decrease and rapid precipitation of ore-forming materials. The late stage fluids, characteristic of low temperature, low salinity, lack of daughter mineral. and poor in CO(2), could be sourced from meteoric water.
Keywords: COLLISIONAL OROGENY; FLUID INCLUSION; MONGOLIA-HINGGAN OROGEN; PORPHYRY CU-MO DEPOSIT; WUNUGETUSHAN